2010
DOI: 10.1289/ehp.0901713
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Porphyrin Excretion in Neurotypical and Autistic Children

Abstract: BackgroundIncreased urinary concentrations of pentacarboxyl-, precopro- and copro-porphyrins have been associated with prolonged mercury (Hg) exposure in adults, and comparable increases have been attributed to Hg exposure in children with autism (AU).ObjectivesThis study was designed to measure and compare urinary porphyrin concentrations in neurotypical (NT) children and same-age children with autism, and to examine the association between porphyrin levels and past or current Hg exposure in children with aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Four uncontrolled case series 126 , 127 , 128 , 129 and seven case–control studies 114 , 130 , 131 , 132 , 133 , 134 , 135 have reported abnormal urinary porphyrin concentrations in children with ASD. One study reported that urinary porphyrin levels were strong predictors of ASD.…”
Section: Resultsmentioning
confidence: 99%
“…Four uncontrolled case series 126 , 127 , 128 , 129 and seven case–control studies 114 , 130 , 131 , 132 , 133 , 134 , 135 have reported abnormal urinary porphyrin concentrations in children with ASD. One study reported that urinary porphyrin levels were strong predictors of ASD.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mitochondrial dysfunctions and changes in porphyrin metabolism have also been reported to occur with higher frequency among ASD patients than in general populations (Rossignol and Frye, 2012;Woods et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increased urinary coproporhyrin (cP), pentacoproporphyrin (5cxP), and the presence of precoprpophyrin (prcP), an atypical porphyrin, which is not found in the urine of unexposed controls, proved Hg toxicity and Hg body burden. Finally, relationships between ASD severity and porphyrin biomarkers of Hg exposure have been described [ 71 , 91 , 92 ].…”
Section: Edcs and Neurodevelopmental Diseases In Humans: Focus On mentioning
confidence: 99%